Building a training program for kindergarten teachers in the light of comprehensive quality standards (Journal of the College of Basic Education, 2022)
Research summary: The teacher is the most prominent element of the educational system, and he is the one who teaches young peopleAnd they are considered as the future human peak of the nation, and this requires raising the level of teacher performance and increasing itIts effectiveness in performing its duties through the preparation of standards for its practices in the areas of administrative leadership and planningTeaching, learning, classroom management, evaluation, etc., and total quality embodies the best method of paymentEducation process The research sample was limited to kindergarten teachersThe survey sample is (100) female teachers; Distributed to the directorates of the soil of Baghdad (Al-Rafah Al-Oula).The second and third) the researcher sent an open questionnaire to them about the overall quality